Indoor air quality (IAQ) in educational institutions: a review on risks of poor IAQ, sampling strategies, and building-related health symptoms - Ismail, Iman Fitri; Adnan, Alif Izzani Zainol; Mohammed Qaid Al-Mekhlafi, Abdulrahman; Mahmoud Abdelkarim Mohamed, Belal Abdelkarim; Nasir, Nurul Fitriah; Hariri, Azian; Mat Isa, Norasikin (FAZ Publishing, 2020)
Health and academic achievement of students from every level of education are affected by the provision of good Indoor Air Quality (IAQ) since the students spend more than 5 hours of a day in school on average. Hence, this paper discusses on issues related to IAQ studies in maintaining a healthy level in educational institution. The presence of indoor pollutants such as VOCs, CO2, and other hazardous elements were assessed in terms of its effects on students’ well-being and health. This paper also examines commonly reported health problems related to poor IAQ such as sick building syndrome (SBS) and asthma. Every measurements and consideration regarding IAQ provision comes with different techniques and strategies, which were highlighted regarding its relative importance and frequency of use by different researchers. The review suggested substitution of natural-based products for indoor cleaning agents and installation of air ventilation and purification systems for a more acceptable indoor air quality.